“Grandfather in the Bones”: Scientific Racism and Anglican Missionaries in Uganda, c. 1900–1930 - Hughes, Rebecca C. (Social sciences and missions, 2020)
Evangelical Anglicans of the Church Missionary Society constructed a triumphal narrative on the growth of the Ugandan Church circa 1900-1920. This narrative developed from racial theory, the Hamitic hypothesis, and colonial conquest in its admiration of Ugandans. When faced with closing the mission due to its success, the missionaries shifted to scientific racist language to describe Ugandans and protect the mission. Most scholarship on missionaries argues that they eschewed scientific racism due to their commitment to spiritual equality. This episode reveals the complex ways the missionaries wove together racial and theological ideas to justify missions and the particularity of Uganda.